Monitoring Ca2+ concentration in living cells - Brini, Marisa (Henry Stewart Talks, 2007)
Introduction to Calcium homeostasis, Synthetic fluorescent Calcium probes, Ratiometric and non-ratiometric probes, Calibration, Recombinant probes: the targeted probes, Aequorin, Targeting strategies, Wide dynamic range, Applications: some examples, GFP-based probes, Advantages and disadvantages, Imaging, FRET based probes